1994
DOI: 10.1007/bf00180527
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of the soluble receptor for tumor necrosis factor in patients with renal disease

Abstract: Tumor necrosis factor-alpha (TNF-alpha) has been found to be elevated in patients during hemodialysis and is thought to mediate some of the immune and metabolic dysfunctions in these patients. It has been speculated that infusions of soluble TNF receptor (sTNF-R) may prevent some of the cytotoxic effects of TNF. However, little is still known about preexisting serum TNF-R levels in patients with chronic renal failure, with or without hemodialysis. Therefore we analyzed serum samples of sTNF-R in 26 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
(11 reference statements)
5
9
0
Order By: Relevance
“…Our results, which showed a significant increase in the sTNF RI concentration as compared to healthy controls, confirm the data from studies performed in adult HD patients [4, 40, 41, 42, 43]. One of the mechanisms leading to an increased blood concentration of this peptide is diminished renal clearance due to CRF resulting in passive accumulation of sTNF RI.…”
Section: Discussionsupporting
confidence: 81%
“…Our results, which showed a significant increase in the sTNF RI concentration as compared to healthy controls, confirm the data from studies performed in adult HD patients [4, 40, 41, 42, 43]. One of the mechanisms leading to an increased blood concentration of this peptide is diminished renal clearance due to CRF resulting in passive accumulation of sTNF RI.…”
Section: Discussionsupporting
confidence: 81%
“…The median level of soluble TNFaR 1 was 2.0 ng/mL in patients with overt nephropathy, similar to that reported in previous studies (2)(3)(4)(5)(6)(7)(8)(9). Circulating levels of soluble TNFaR 1 were highly correlated with eGFR (R 2 = 0.69) (Supplementary Fig.…”
Section: Circulating Levels Of the Soluble Tnfarsupporting
confidence: 88%
“…1B and Supplementary Table 2). Notably, however, the cause-specific (Cox) model had statistical (overall fit) advantage compared with the competing risk (Fine-Gray) model, as assessed by the difference in respective BIC (1,256 vs. 1,220; threshold for difference of [5][6][7][8][9][10]. This may be understood in that the cause-specific Cox model has inferential advantage with respect to pathophysiology, whereas in a therapeutic/trial sense, a competing risk model may be apposite.…”
Section: Discussionmentioning
confidence: 99%
“…The soluble TNFR levels have been reported to be increased during acute rejection. [20][21][22][23][24] In accordance with these studies, we observed significant elevation of serum TNFR2 levels in acute rejection. Regarding ROC analysis for estimating acute rejection, serum TNFR1 and TNFR2 levels determined on 7th day and first month have highest sensitivity and specificity in our study.…”
Section: Discussionsupporting
confidence: 85%